Математика и живая природа. Удивительный мир ДНК - Гупал, А.М.; Вагис, А.А. (Проблемы управления и информатики, 2006)
Обгрунтовано, що жива природа розвивається на основі індуктивних механізмів. У геномі людини в зашифрованому вигляді містяться ефективні індуктивні процедури, що керують генами і модифікують їх. It is justified that the living nature is progressing on the basis of inductive mechanisms. In the encoded form, effective inductive procedures, which control genes and modify them, are contained in human genom.